Grouping Sales Levels Smartphone Of Offline Store Using BIRCH Clustering Algorithm - Rahmadani Sari, Putri Dwi; Qamal, Mukti; Rosnita, Lidya (Department of Information Technology, Universitas Malikussaleh, Aceh Utara, Indonesia, 2024)
From 2020 to 2024, TM_Store and Jaya Com exhibited different sales patterns based on cluster analysis using the BIRCH algorithm. The background of this research is to provide strategic insights to both stores for improving their sales performance through data analysis. The sales data used includes brand, type, month, year, stock quantity, quantity sold, unit price, and total sales. The BIRCH method was chosen for its effectiveness in handling large datasets and providing accurate clustering results. The clustering results indicate a significant increase in the